Post-Traumatic Stress Disorder after the 6.1 Magnitude Earthquake in Piura, Peru: A Cross-Sectional Study - Valladares-Garrido, Mario J. (2022)
“: In Peru, major disasters like the 2007 Pisco earthquake have produced high rates of posttraumatic stress. However, evidence is still needed to strengthen interventions. In 2021, a major earthquake struck Piura, in northern Peru. In this context, we aimed to assess the prevalence of PTSD and its associated factors. A cross-sectional study was conducted during August–September 2021 in people who experienced the 6.1 Piura earthquake on 30 July 2021. The questionnaire included the PCL-C, CD-RISC, ISI, HFIAS, and additional demographic data. Generalized linear models were used. The prevalence of PTSD was 20.3%. Household income was between PEN 2001 and 3000 (PR = 4.26, 95% CI: 1.08–16.75), smoking (PR = 2.49, 95% CI: 1.03–6.01), experience of a nervous breakdown (PR = 1.83, 95% CI: 1.09–3.09), moderate food insecurity (PR = 2.91, 95% CI: 1.10–7.73), and severe insomnia (PR = 8.25, 95% CI: 2.22–30.71) increased the prevalence of PTSD. One out of five individuals experienced post-traumatic stress symptoms after the 2021 earthquake in Piura, which varies depending on socioeconomic, psychosocial, and individual factors. Further research should strengthen these findings to ensure a fair and early mental health intervention against new seismic events in this and other Peruvian regions.“